Stachytarpheta serrana, a new species of Verbenaceae endemic to the Diamantina Plateau in Espinhaço Range (Minas Gerais, Brazil), with palynological and anatomical notes - PEDRO HENRIQUE CARDOSO; FÁTIMA REGINA G. SALIMENA; ANDREA P. LUIZI-PONZO; NÁDIA SOMAVILLA; PÂMELA T. PATRÍCIO; MARCELO TROVÓ (Anais da Academia Brasileira de Ciências)
Abstract Stachytarpheta serrana, a new Brazilian species from the Serro municipality in the campos rupestres of the Diamantina Plateau, Minas Gerais state, is described and illustrated. Like most species of the genus found in this region, S. serrana has blue corollas and is morphologically related to S. glabra. Its recognition as a distinct species is supported by morphological, palynological, and anatomical evidence. The main traits for its recognition are its erect or suberect leaves, amphistomatic, with a foveolate abaxial surface and hirsute veins forming a reticulate network, flowers with a calyx 1.3–1.6 cm long and a corolla tube 2.3–2.6 cm long, subprolate pollen grains with a granulate colpi membrane, and fruits with a short beak at the apex. With a restricted distribution and known from only two recent collections, S. serrana should be classified as Data Deficient (DD).